Liposomal preparations of muramyl glycopeptides as immunomodulators and adjuvants - Turánek, Jaroslav; Ledvina, Miroslav; Kasná, Andrea; Vacek, Antonín; Hríbalova, Vera; Krejcí, Josef; Miller, Andrew D (Vaccine, 2006)
The need for safe and structurally defined immunomodulators and adjuvants is increasing in connection with the recently observed marked increase in the prevalence of pathological conditions characterized by immunodeficiency. Important groups of such compounds are muramyl glycopeptides, analogs of muramyl dipeptide (MDP), glucosaminyl-muramyl dipeptide (GMDP), and desmuramylpeptides. We have designed and synthesized new types of analogs with changes in both the sugar and the peptide parts of the molecule that show a high immunostimulating and adjuvant activity and suppressed adverse side effects. The introduction of lipophilic residues has also improved their incorporation into liposomes, which represent a suitable drug carrier. The proliposome-liposome method is based on the conversion of the initial proliposome preparation into liposome dispersion by dilution with the aqueous phase. The description of a home-made stirred thermostated cell and its link-up with a liquid delivery system for a rapid and automated preparation of multilamellar liposomes at strictly controlled conditions (sterility, temperature, dilution rate and schedule) is presented. The cell has been designed for laboratory-scale preparation of liposomes (300-1000 mg of phospholipid per run) in a procedure taking less than 90 min. The method can be readily scaled up. Examples of adjuvant and immunostimulatory effect of liposomal preparation in mice model will be presented.
Keywords: Mice; adjuvancia imunologická; Liposomes; Animals; Acetylmuramyl-Alanyl-Isoglutamine; Adjuvants, Immunologic; zvířata; myši; acetylmuramyl-alanyl-isoglutamin; liposomy